2022
DOI: 10.1088/1402-4896/acac54
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the structural and magnetic trends in Ba0.9Sm0.1Fe12−xAlxO19 M-type Hexaferrites

Abstract: Current study describes the structural and magnetic properties of Ba0.9Sm0.1Fe12-xAlxO19 (x=0.0, 0.5, 1.0, 2.0, 3.0) M-type hexaferrites. Conventional ceramic route was implied to prepare all the nominal samples. Morphological analysis suggested the non-presence of secondary phases as well as formation of the hexaferrites material. X-ray Diffraction technique was used for structural analysis from which microstructural parameters are calculated and discussed. Magnetic properties are measured at room temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…The results showed that there were no secondary phases in the material and that the hexagonal shape of the particles was evident in the micrographs. The SEM images in figure 2 was also confirmed that the samples were homogenously and uniformly distributed [18,30]. Pores present in the images showed the removal of PVA binder.…”
Section: Morphological Analysissupporting
confidence: 58%
See 1 more Smart Citation
“…The results showed that there were no secondary phases in the material and that the hexagonal shape of the particles was evident in the micrographs. The SEM images in figure 2 was also confirmed that the samples were homogenously and uniformly distributed [18,30]. Pores present in the images showed the removal of PVA binder.…”
Section: Morphological Analysissupporting
confidence: 58%
“…Various research studies have been carried out to enhance the hard magnetic properties of M-type hexaferrites by substituting alternative cations for those found in Ba or Fe sites [1,3,10,15,18]. For instance, the research conducted on the BaFe 12−x Al x O 19 using a sol-gel self-combustion method showed the coercivity of the substance reached a high of 13.7 kOe.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrate that the prepared material is significant for magnetic purposes, including spintronics, magnetic filters, and recording media. The magnetic moment per formula unit is determined using the formula below for Bohr's magnetron [34].…”
Section: Vsm Resultsmentioning
confidence: 99%
“…Cell refinement analysis of the synthesized samples of M-type BaFe 11.5−x Al 0.5 Co x O 19 (x = 0.00, 0.5, 1.0, 1.5, and 2.0) hexaferrites nanoparticles was performed by Celref software [10,45,46]. Lattice parameters of all the produced samples were listed in table 1.…”
Section: Structural Investigationmentioning
confidence: 99%
See 1 more Smart Citation